AB0856 RISK FACTORS OF CIRRHOSIS- RELATED OSTEOPOROSIS. (June 2019) - Trad, Nouha; Issaoui, Dhilel; Kchir, Hela; Soua, Sabrine; Chaabouni, Hatem; Maamouri, Nadia
Abstract : Background: Osteoporosis, that may lead to a high risk of fractures and compromises quality of life, is the main bone disturbance among cirrhotic patients. Despite that, it tends to be under-diagnosed. Objectives: To determine frequency of osteoporosis and identify risk factors associated among cirrhotic patients. Methods: We performed a retrospective analysis of data from consecutive cirrhotic patients recruited from January 2010 to December 2017 and who had at least one bone mineral density measurement (BMD). By definition from the World Health Organization, osteoporosis is defined by bone densitometry as a T score < -2.5 and osteopenia as a T score between -1 and -2.5. Results: 227 patients with an average age of 65.5 years [24-90] were included. Thirty one had a BMD: ten patients with HCV-related cirrhosis (HCV), seven patients with HBV-related cirrhosis (HBV) and 14 patients with autoimmune liver disease (eight cases of primary biliary cholangitis (PBC), two cases of primary sclerosing cholangitis (PSC), two cases of autoimmune hepatitis (AIH) and two cases of overlap syndrome (PBC+AIH)).. Osteopenia was observed in seven patients (22.5%): three cases of HCV, two cases of PSC and two cases of overlap syndrome. 17 patients had an osteoporosis (54.8%): six cases of HCV, three cases of HBV, five cases of PBC, two cases of AIH and one case of PSC. Osteoporosis is most common in postmenopausal women with significant correlation (p<0, 001). Hyperbilirubinaemia and increased Gamma Glutamyl Transferase (GGT) were significantly correlated with osteoporosis (p<0.05). However, there was no significant correlation between osteoporosis and body mass index or the Child-Pugh score. Conclusion: In our study, 54.8% of cirrhotic patients who have had a BMD, had an osteoporosis. It was more frequent among postmenopausal women with hyperbilirubinaemia and increased GGT. The systematic realization of BMD in these patients could contribute to better management. Disclosure of Interests: None declared